Advancements and innovations in keratoconus management: a review of current practices - Son, Hyeck Soo; Friedrich, Maximilian; Jun, Albert S.; Soiberman, Uri S. (Journal of Clinical Medicine, 2025)
Keratoconus is a potentially blinding condition characterized by progressive thinning and steepening of the cornea, leading to visual impairment due to irregular astigmatism and myopia. While the exact pathophysiology is still unknown, it is believed to involve genetic, environmental, and cellular factors. Treatment options for keratoconus have significantly expanded over the past few decades. Historically, glasses were the primary means of managing mild cases, whereas rigid gas permeable contact lenses were used in moderate to advanced diseases; yet the latter were rarely tolerated by patients with steep cones, in which full-thickness corneal transplantation was often performed. However, a variety of innovative treatments have been introduced in the past decades. Corneal collagen cross-linking (CXL) has revolutionized the field by halting the progression of keratoconus through creating new covalent bonds between individual corneal fibers. Custom, soft, and scleral contact lenses have improved visual outcomes for many patients. Additionally, surgical interventions such as intrastromal ring segments and Bowman layer transplantation have provided alternatives for visual restoration and postponing a potential keratoplasty. Furthermore, innovative cellular and pharmacological KCN treatments are on the horizon, awaiting clinical trials. This review article aims to provide a comprehensive overview of the current treatment options for keratoconus.
Gesehen am 27.02.2026
Keywords: Rezension